One Step Forward, Two Steps Back: Is Israeli-Arab peace possible so long as the Christian Zionist narrative is upholding the peace talks? - Kirkland, Caroline Miller (Columbia Undergraduate Research Journal, 2020)
Peace efforts in Palestine are continuous and failing. In order to explain the failed peace attempts, experts draw different conclusions. Thomas Getman, member of a private consulting group specializing in international affairs, explains the conflict in terms of Christian Zionism, a religious doctrine prominent in the United States, and its detrimental role in the peace process. While social justice manifests itself in the cultural practices of traditional, mainstream religions, Christian Zionism ignores the rights-based approach to theology, and it perpetuates myths (Getman). Dennis Ross, the principle informant in the Israeli-Arab conflict under the Bush and Clinton administrations, blames a number of factors. He explains, “The lack of public conditioning for peace, the reluctance to acknowledge the legitimacy of the other side’s grievance and needs, the inability to confront comfortable myths, the difficulty of transforming behavior and acknowledging mistakes, the inherent challenges of getting both sides ready to move at the same time, the unwillingness to make choices, and the absence of leadership, especially among Palestinians, are all factors that have made peace difficult to achieve” (Ross 14). Ultimately, Ross says that it is “myths that prevent all sides from seeing reality and adjusting to it” (Ross 14). The failed peace efforts can be better understood by combining the two stances. Due to the stronghold Christian Zionism has held on United States politics, the Christian Zionist narrative has upheld peace talks in Israel-Palestine and disrupted the process.